2018
DOI: 10.1007/s11274-018-2452-5
|View full text |Cite
|
Sign up to set email alerts
|

Succession of bacterial microbiota in tilapia fillets at 4 °C and in situ investigation of spoilers

Abstract: The succession of bacterial microbiota in tilapia fillets during cold storage at 4 °C was investigated employing PCR-DGGE method. Results showed that Pseudomonas was the most dominant genus during entire storage period. Shewanella and Psychrobacter were also always present, but became dominant only after 3 days of storage. Acinetobacter, Brevibacterium, Flavobacterium, Dietzia and Janthinobacterium were always the minor genera, among which Acinetobacter and Brevibacterium disappeared 6 days later, and Dietzia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
2
10
1
Order By: Relevance
“…To some extent, the bacterial genera found at 4 °C in this research differ from the findings of the authors’ previous research (Duan et al., ), which found Pseudomonas to be the most dominant genus throughout the storage process, while Shewanella and Psychrobacter were only found to be dominant after 3 days of storage, and Acinetobacter , Brevibacterium , Flavobacterium , Dietzia , and Janthinobacterium were the minor genera throughout all periods of detection. Yet, it is important to note that different sources of the tilapia fillets were used in the present and previous researches.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…To some extent, the bacterial genera found at 4 °C in this research differ from the findings of the authors’ previous research (Duan et al., ), which found Pseudomonas to be the most dominant genus throughout the storage process, while Shewanella and Psychrobacter were only found to be dominant after 3 days of storage, and Acinetobacter , Brevibacterium , Flavobacterium , Dietzia , and Janthinobacterium were the minor genera throughout all periods of detection. Yet, it is important to note that different sources of the tilapia fillets were used in the present and previous researches.…”
Section: Resultscontrasting
confidence: 99%
“…Finally, the amplified 16S rDNA fragments were analyzed by DGGE according to the method outlined in Duan et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the techniques used in the research were suitable for the purpose of the study due to the cost, time and prior knowledge required to perform the analysis. Duan et al (2018) investigated the succession of bacterial microbiota in tilapia fillets during cold storage at 4°C applying the PCR-DGGE method.…”
Section: Denaturation Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%